Vulvar schwannoma: a case report - Bafna, Barkha; Bafna, Amit; Bafna, Ashalata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Schwannoma is a benign, slow growing nerve sheath neoplasm that is rarely found in female genital system. Only a few cases of vulvar schwannomas have been reported. We report a case of vulvar Schwannoma arising in labium minus in a patient without neurofibromatosis. A 26 year old woman had two 1cm x 1cm and 1.5cm x 2cm sized oval nodules at the right labium minus. Complete excision was done and the histological report confirmed to be vulvar Schwannoma. Although it has a very low incidence, Schwannoma should be considered as a differential diagnosis of a vulvar mass.